(untitled) (Latakia University Journal -Basic Sciences Series, 2018)
نظراً للاهتمام الحالي الكبير للمركبات المتفسفرة عالية الإصدار الضوئي في مجال الأطوال الموجية الكبيرة (550-1050nm) ولتطبيقاتها الواسعة في مختلف المجالات الفيزيائية (فيزياء اللايزر-فيزياء أنصاف النواقل-الفيزياء الطبية والتصوير المقطعي الطبقي....الخ). ونظراً لكون طيف الإصدار الضوئي لهذه المركبات متوافقاً مع حساسية الثنائيات الضوئية من السيليكون، فقد بينا في هذه المقالة مميزات زمن التضاؤل والزمن الطيفي لبعض المركبات المتفسفرة ذات الأطوال الموجية الطويلة مثل:AL2O3:Ti, APB VI وبعض الموليبدات, Y2O2S وGd2O2S مع Tb ومواد أخرى. كذلك تم دراسة انتقال سويات الطاقة نحو مراكز التألق وعلاقتها بالانتقالات النسبية. At present there is a great interest in phosphors producing high light yield in long wavelength region (550-1050nm). They have a lot of application in different fields of physics such as laser physics, medical physics and tomography, semiconductor physics and others. The main reason of that is the emission spectra of these materials matches well to sensitivity of silicon photodiodes. In this paper we present the spectral and decay time characteristics of some long –wavelength phosphors (such as AΠ BVI, AL2O3:Ti, some molybdates, Gd2O2S and Y2O2S doped with Tb, and some others). The process of energy transfer to emission centers is considered. In most cases, types of centres responsible for radiative transitions were determined.